Prevalence of anophthalmia etiological factors in patients treated in a reference center: A retrospective study - Penitente, Paulo Augusto [UNESP]; Freitas da Silva, Emily Vivianne [UNESP]; Pontes Manicoba, Lorena Louise [UNESP]; Azevedo Romero, Giovana Dornelas [UNESP]; Micheline dos Santos, Daniela [UNESP]; Goiato, Marcelo Coelho [UNESP] (Elsevier, 2021)
Background: Ocular prosthesis rehabilitation has an important social, psychological, esthetic, and functional role. Congenital factors, trauma, and tumors, among others, can cause anophthalmia, and it is essential to identify the etiology to guide its prevention and treatment. Methods: The aim of this study was to retrospectively investigate the records of patients treated from 2013 to 2020 by the Oral and Maxillofacial Prosthesis Group, aiming to identify the prevalence of patients with anophthalmia and the etiology of their anophthalmia. After approval by the Human Research Ethics Committee, two calibrated researchers evaluated 520 records, identifying those from patients with anophthalmia. The inclusion criteria were records with complete and legible information from patients with anophthalmia and a description of their etiology. Descriptive statistics were performed, and etiological factors were categorized into trauma, congenital cause, end-stage eye disease, and tumor. Spearman's correlation was performed to verify the relation between gender and anophthalmia etiology, with a 5% significance level. Seventy-two records were included in the study. Results: It was observed that 33.4% of patients were women and 66.6% were men. The etiologies were physical trauma (52.4%), tumor (21.8%), end-stage eye disease (16.6%), and congenital cause (9.2%), and there was no correlation between gender and these etiologies (p =.301). Conclusion: Most of the cases identified were of traumatic origin, which allows the establishment of preventive and educational measures to avoid new cases of anophthalmia.
Keywords: Anophthalmia; Artificial eye; Eye; Eye diseases; Ocular prosthesis